2007
DOI: 10.1007/s11199-006-9168-y
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about Chastity, Machismo, and Caste Identity: A Cultural Psychology of Gender

Abstract: The study was conducted with a community sample (N=1118) of participants from three caste groups (Brahmins, Thevars, and Gounders) from villages that are reported to have an extremely male-biased sex ratio in Tamilnadu, India. Chastity, Machismo, and Caste Identity scales were used to assess cultural beliefs about gender and caste. The correlations among beliefs about caste identity, chastity, and machismo were significant for all three caste groups. There was a significant difference between Brahmins and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 21 publications
1
42
0
Order By: Relevance
“…As Indira Gandhi stated, Indian women are "the conserver of tradition but also the absorber of the shock of the future […] ensuring the continuity which strengthens roots and simultaneously engineering change" (cited by Jung 1987). Our results are also in line with a study conducted in another state of India, Tamilnadu (Mahalingam 2007). This study revealed that women presented a stronger caste identity than men.…”
Section: Discussionsupporting
confidence: 92%
“…As Indira Gandhi stated, Indian women are "the conserver of tradition but also the absorber of the shock of the future […] ensuring the continuity which strengthens roots and simultaneously engineering change" (cited by Jung 1987). Our results are also in line with a study conducted in another state of India, Tamilnadu (Mahalingam 2007). This study revealed that women presented a stronger caste identity than men.…”
Section: Discussionsupporting
confidence: 92%
“…The Cronbach's alpha for the chastity scale was .92. The reliability for the chastity scale in previous studies is comparable (Mahalingam 2007b; Cronbach's alpha=.90).…”
Section: Chastity Scalementioning
confidence: 58%
“…We employed the following scales to measure idealized beliefs about gender: beliefs about chastity (Mahalingam 2007b) and idealized beliefs about masculinity (Cueller et al 1995). To measure resilience, the John Henryism scale was utilized, which assesses behavioral disposition to engage high effort coping with challenging psychosocial and environmental barriers to success (James et al 1983;James 1994).…”
Section: Methodsmentioning
confidence: 99%
“…When access to power was manipulated in the laboratory, Fiske [1993] found that power holders used category-based (i.e., essentialized) information whereas their subordinates used more contextual, idiosyncratic information to make judgments about an applicant. In a community-based quantitative study about culture-specific essentialist beliefs about gender, such as chastity, Mahalingam [2007b] found that men scored higher on essentialist beliefs about chastity and masculinity than women. There are several examples of marginalized group members endorsing essentialist representations of dominant groups [Jost, 1995] using his system justification theory, Jost [1995] showed that often subordinate group members internalize and accept dominant ideologies to facilitate the smooth functioning of their social system.…”
Section: Essentialism Power Folk Sociology and Life Span Developmentmentioning
confidence: 99%